Flight activity of stingless bees Tetragonisca angustula (Hymenoptera: Apidae: Meliponini) during in the year - Malerbo-Souza, Darclet Teresinha; Halak, André Luis (ENTOMOTROPICA, 2016)
The aim of this experiment was to study the external activity of Tetragonisca angustula through out the year and its relation with air temperature and relative humidity. Material was collected in the Centro Universitário Moura Lacerda, Ribeirão Preto, SP. Once a month, for twelve months, an assessment was made by recording the number of bees entering the colonies with nectar or with pollen in corbiculae between 7:00 a.m. and 6:00 p.m., during 10 minutes each time (hour). There were significant differences in external activity of T. angustula along the 12 months of observation. Bees entering without loads of pollen were most numerous in March 2008 and least in July 2007. Bees entering with loads of pollen peaked in February 2008 and showed lowest activity level in July 2007. T. angustula is very sensitive to air temperature. External activity without loads of pollen starts with 17.8 °C with activity peaks between 25.0 and 35.3 °C. Bees entering with loads of pollen needed higher temperature (19.6 °C) for beginning external activity, and showed peaks between 23.7 and 34.4 °C. Relative humidity is not a limiting factor for the foraging behavior of T. angustula. Frequencies for bees entering nests without loads of pollen was 86.3 %, for bees with pollen 13.7 %.